O investimento em bens no Estado do Ceará, com base nas notas fiscais eletrônicas - Rodrigues, Matheus Cargnin (2024)
This study aims to estimate the Gross Fixed Capital Formation (GFCF) matrix for goods in the state of Ceará, covering the period from 2013 to 2019, based on data from Electronic Invoices (NF-e). The adopted methodology involved classifying transactions of purchases and sales of goods intended for fixed assets by companies based in the state, considering interstate, internal, and import operations. Fiscal codes for operations and services (CFOP) were used to identify transactions related to fixed assets, allowing for a detailed analysis of investment dynamics in the state. The results reveal significant variations in the GFCF balance over the years, reflecting economic dynamics and the impacts of recent economic crises. A downward trend in the GFCF balance was observed since 2015, except in 2018, which saw a significant increase due to a positive shock in industrial investments. The analysis highlighted the importance of the industrial and electricity, gas, water, and sewage sectors. Section XVI (Machinery and Equipment, Electrical Material and their Parts) remained the main recipient of investments, driven by major industrial projects.